2022
DOI: 10.1021/acs.orglett.2c03458
|View full text |Cite
|
Sign up to set email alerts
|

Manganese-Catalyzed Regioselective C–H Lactonization and Hydroxylation of Fatty Acids with H2O2

Abstract: Herein, we report the direct selective C−H lactonization of fatty acids (C5−C16), catalyzed by manganese(II) complexes bearing bis-amino-bis-pyridine ligands. The catalyst system uses the environmentally benign hydrogen peroxide as oxidant and exhibits high efficiency (100−200 TON), providing under optimized conditions γ-lactones in 60−90% yields. Remarkably, by changing the reaction conditions, the oxidation of hexanoic acid can be diverted toward formation of δcaprolactone in up to 67% yield. Furthermore, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Inspired by the SCS hydrogen bonding in metallooxygenases (Figure C), , and encouraged by hydrogen bond donor solvents in oxidation catalysis, we envisioned that SCS hydrogen bonding between the hydrogen bond donor solvent and the basic nitrogen atom would not only protect the nonheme manganese catalyst from arrest but also deactivate the basic nitrogen atom toward oxygen atom transfer (OAT) and the α-C­(sp 3 )–H bonds adjacent to nitrogen center toward H-atom abstraction (HAA) by electrophilic oxidant, thus addressing the challenges from catalyst deactivation and competitive nitrogen oxidation and C­(sp 3 )–H oxidation mediated by highly electrophilic high-valent metal–oxo intermediates (Figure D). We report herein an SCS solvent hydrogen bonding strategy to realize the remote and nonactivated C­(sp 3 )–H hydroxylation in the presence of basic N -heteroaromatics with low loadings of a simple nonheme manganese complex as catalyst and aqueous H 2 O 2 as a terminal oxidant (Figure D).…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the SCS hydrogen bonding in metallooxygenases (Figure C), , and encouraged by hydrogen bond donor solvents in oxidation catalysis, we envisioned that SCS hydrogen bonding between the hydrogen bond donor solvent and the basic nitrogen atom would not only protect the nonheme manganese catalyst from arrest but also deactivate the basic nitrogen atom toward oxygen atom transfer (OAT) and the α-C­(sp 3 )–H bonds adjacent to nitrogen center toward H-atom abstraction (HAA) by electrophilic oxidant, thus addressing the challenges from catalyst deactivation and competitive nitrogen oxidation and C­(sp 3 )–H oxidation mediated by highly electrophilic high-valent metal–oxo intermediates (Figure D). We report herein an SCS solvent hydrogen bonding strategy to realize the remote and nonactivated C­(sp 3 )–H hydroxylation in the presence of basic N -heteroaromatics with low loadings of a simple nonheme manganese complex as catalyst and aqueous H 2 O 2 as a terminal oxidant (Figure D).…”
Section: Introductionmentioning
confidence: 99%
“…Some of us examined the lactonization of fatty acids, mediated by a series of non‐heme Mn complexes (Figure 1) and found that the reaction exhibits tunable regioselectivity (Figure 11). [10d] Interestingly, γ ‐lactonizations in the presence of catalyst 9 b showed the best lactone yields and γ/ δ ratios in the absence of strong Brønsted acids. Contrastingly, adding those (and reducing the temperature) diverted the regioselectivity towards δ ‐caprolactone (in the case of caproic acid) or towards the elusive ( ω ‐1)‐hydroxy derivatives (in the case of acids with longer main chain).…”
Section: Oxidations That Enable Direct Inter‐ and Intramolecular Acyl...mentioning
confidence: 96%
“…Contrastingly, adding those (and reducing the temperature) diverted the regioselectivity towards δ ‐caprolactone (in the case of caproic acid) or towards the elusive ( ω ‐1)‐hydroxy derivatives (in the case of acids with longer main chain). This regio‐ and chemoselectivity switch was tentatively explained by changing the reaction mechanism: from carboxylic acid‐directed mechanism, leading to γ ‐lactonization, to undirected one, resulting in the hydroxylation at the most electron‐rich methylenic site (with further intramolecular esterification in the case of caproic acid) [10d] …”
Section: Oxidations That Enable Direct Inter‐ and Intramolecular Acyl...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have demonstrated that Mn complexes 3 and 4 are efficient catalysts of selective C–H oxyfunctionalizations with hydrogen peroxide. Herewith, these catalyst systems have been tested in asymmetric epoxidations.…”
Section: Epoxidation Of Olefins In the Presence Of Benzhydryl-substit...mentioning
confidence: 99%